Parenting Style to Build Children as Memorizers of the Qur’an - Sri Nur Rahmi; Adam Mudinillah; Desty Ayu Anastasha; Samsul Susilawati (Yayasan Adra Karima Hubbi, 2024)
The family is the place where a child gets the first education before school. However, many parents do not care about the development of their children’s education, especially in getting closer to the Qur’an. Currently, the Qur’an memorization program is developing rapidly, judging from the number of tahfidz houses that have been established. So it takes the role of parents in building their children as memorizers of the Qur’an. The purpose of this study is to find out how the parenting style of parents to build children as memorizers of the Qur’an. This study uses a qualitative descriptive method. The subjects of the research are parents and their children. Data collection techniques are carried out through interviews and observations. The results of the study show that the parenting style carried out by parents in fostering children as memorizers of the Qur’an is often reading the Qur’an since the child is in the womb, listening to murottal at all times, helping children memorize every time they finish the dawn prayer, helping children leave their memorization every afternoon before Maghrib and choosing a good school to support the Qur’an memorization program in children. This parenting style can help children memorize the Qur’an 1 juz within 40 days so as to build children as memorizers of the Qur’an.